Development Strategy of Klanceng Honey Livestock (Trigona Sp) in Lubuk Raja, Ogan Komering Ulu District - Jonson, Rhobet; Efrianti, Rini; Oktarina, Yetty; Novayanti, Novayanti (ITScience (Information Technology and Science), 2024)
Honey bee cultivation is one of the livestock businesses that can play a role in meeting the economic needs of the community. This research was conducted in order to find out what strategies are appropriate in developing the Klanceng (Trigona sp) honey livestock business so that the marketing and development of the Klanceng (Trigona sp) honey livestock business can develop and be able to add economic value to the people of Lubuk Raja District, Ogan Komering Ulu Regency. The results of this research are internal factors include strengths and weaknesses, namely that employees have undergone training, the availability of nectar production facilities is quite extensive, cultivation management has been implemented and they already have market share. The weaknesses of the Klanceng Honey Farming Business (Trigona SP) in Lubuk Raja District, Ogan Komering Ulu Regency are seasonal factors, funds, not being able to harvest every day, simple product packaging and lack of knowledge of marketing media. External factors include opportunities and threats. The strategiesis using the S-O strategy or power of opportunity strategy, namely utilizing government support in expanding the marketing area for honey products, utilizing nearby shops and honey collecting agents to market the harvest of Klanceng honey bee products (Trigona sp), then utilizing social media as a promotional tool honey products, as well as changing old packaging in the form of marjan bottles into more attractive glass bottles, developing technology for cultivating livestock Klanceng honey bees (Trigona sp) and finally renting land in an area that is in season.